2016
DOI: 10.1021/acs.jpcc.6b09687
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy as a Descriptor of Catalytic Activity

Abstract: Computational searches for catalysts of the hydrogen evolution reaction commonly use the hydrogen binding energy (HBE) as a predictor of catalytic activity. Accurate evaluation of the HBE, however, can involve large periodic supercell slab models that render high-throughput screening relatively expensive. In contrast, calculations of other relevant surface properties, such as the surface energy, work function, and potential of zero charge (PZC), require only small surface unit cells and are hence less expensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 73 publications
4
94
0
Order By: Relevance
“…[28] However, Zhuang et al found that activity and stability do not always obey this relationship, and surface stability that is too high or too low corresponds to poor HER activities for metal or transition metal carbides. [29] Recent experimental results also verify that balancing of the activity and stability is possible for nanoporous core-shell iridium/iridium oxide for oxygen evolution catalysts. [30] The results of the present study indicate that bridge Ni 2 Ni 3 of the (111)C is the most active (ΔG H* ¼ 0) and unstable (6 coordination number).…”
Section: The Relationship Between Activity and Stabilitymentioning
confidence: 80%
See 3 more Smart Citations
“…[28] However, Zhuang et al found that activity and stability do not always obey this relationship, and surface stability that is too high or too low corresponds to poor HER activities for metal or transition metal carbides. [29] Recent experimental results also verify that balancing of the activity and stability is possible for nanoporous core-shell iridium/iridium oxide for oxygen evolution catalysts. [30] The results of the present study indicate that bridge Ni 2 Ni 3 of the (111)C is the most active (ΔG H* ¼ 0) and unstable (6 coordination number).…”
Section: The Relationship Between Activity and Stabilitymentioning
confidence: 80%
“…Danilovic et al also indicate that the degree of activity is inversely proportional to the stability . However, Zhuang et al found that activity and stability do not always obey this relationship, and surface stability that is too high or too low corresponds to poor HER activities for metal or transition metal carbides . Recent experimental results also verify that balancing of the activity and stability is possible for nanoporous core‐shell iridium/iridium oxide for oxygen evolution catalysts .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant experimental and DFT studies have been carried out to demonstrate the both polycrystalline, and well‐defined closed pack platinum surfaces revealing the fact that the HER activity varies with the site and geometrical orientations . Due to its high price and a shortage of Pt; many efforts via nanosizing, and alloying have been taken place to make it more suitable for commercial applications in recent years …”
Section: Introductionmentioning
confidence: 99%